Promoting research integrity in a global environment - Mayer, Tony; Steneck, Nicholas (World Scientific Publishing Co. Pte. Ltd, 2011)
Globalisation has become a rewarding but challenging fact of life for scientific and scholarly researchers. Intellectually, they work with shared understandings of their areas of research and research methods. Professionally, responsibility and best practices are subject to many different rules and standards that vary across disciplines, countries, and cultures. They know how to measure and study the objects of their research but are often less sure of what constitutes the responsible practice of research or research integrity.